REINTERPRETATION TO BALANCE IN INHERITANCE DISTRIBUTION ON BILATERAL KINSHIP IN ACEH (International Seminar on Syariah and Law (INSLA), 2020)
The study aims at describing inheritance distribution among Acehnese, balance in inheritance distribution, and reinterpretation to balance in inheritance distribution in a society with bilateral kinship system. This research is a normative research with a juridical approach, with a focus on studies in three locations; Pidie, North Aceh and South Aceh, with primary and secondary data sources, then analyzed descriptive analytic. The results indicate that inheritance law among Acehnese is mainly based on faraid (inheritance distribution) law. Nevertheless, in its development and implementation, there are cases in which the distribution is a result of familial agreement. In general, both male and female heirs have the same rights in inheritance distribution—a common character in bilateral kinship. In the distribution of assets, it was found that Hareuta Peunulang's assets were found, these assets could later be counted as an inheritance. In Acehnese perspective especially in South Aceh, local tradition can decide the position of inheritance and the role of ninik mamak (respected elders), similar to Minangkabau’s tradition which adheres to matrilineal kinship. It indicates a tendency among Acehnese to adopt matrilineal system, even though it mainly relies on bilateral system. In maqasid sharia’s viewpoint, waqf aims at preserving the wellbeing of waqif’s offspring. Acehnese inheritance law is actually in-line with Aristotle's Theory of Justice, in which fairness is a situation where people should apply rules the same and treat similar cases alike.